2017
DOI: 10.1186/s13287-017-0646-7
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent mesenchymal stromal cells enhance insulin secretion from human islets via N-cadherin interaction and prolong function of transplanted encapsulated islets in mice

Abstract: BackgroundMultipotent mesenchymal stromal cells (MSC) enhance viability and function of islets of Langerhans. We aimed to examine the interactions between human MSC and human islets of Langerhans that influence the function of islets.MethodsHuman MSC and human islets (or pseudoislets, obtained after digestion and reaggregation of islet cells) were cocultured with or without cellular contact and glucose-stimulated insulin secretion assays were performed to assess cell function. The expression of several adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 40 publications
5
45
0
Order By: Relevance
“…porosity, stability and permeability were fulfilled by alginate [50]. Consistent results by several studies were reported that pancreatic islet, ESC-and iPSC-derived IPC encapsulation using alginate could maintain the viability both in vivo and in vitro [51][52][53][54][55][56]. Another study on pancreatic islet cryopreservation incorporated alginate encapsulation reported that alginate encapsulation could maintain both viability and functionality of pancreatic islets [57].…”
Section: Discussionsupporting
confidence: 63%
“…porosity, stability and permeability were fulfilled by alginate [50]. Consistent results by several studies were reported that pancreatic islet, ESC-and iPSC-derived IPC encapsulation using alginate could maintain the viability both in vivo and in vitro [51][52][53][54][55][56]. Another study on pancreatic islet cryopreservation incorporated alginate encapsulation reported that alginate encapsulation could maintain both viability and functionality of pancreatic islets [57].…”
Section: Discussionsupporting
confidence: 63%
“…We have identified MSC‐derived soluble secretory products that mimic some of the beneficial effects of MSCs in vitro, and shown that preculturing islets with a defined cocktail of MSC‐secreted ligands also improved islet graft function in vivo, albeit not to the same extent seen with MSC coculture . MSC‐derived extracellular matrix further contributes to the beneficial effects of MSCs on islet function, and a number of studies have highlighted the importance of direct MSC‐islet cell‐cell contact for islet functional survival . Studies in other tissues have also demonstrated the capacity of MSCs to act as mitochondria donors by transferring functional mitochondria directly to adjacent cocultured cells in inflammatory and ischemic disease settings, resulting in the rescue of aerobic respiration .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the use of transgenic pigs led to comparable results in vascularized heterotopic heart xenografts . Another potential strategy, namely encapsulation of pig islets , should also benefit from further development of genetically modified pigs. Of note, islet xenotransplantation from nongenetically modified pig‐to‐human achieved islet survival but no significant clinical improvement .…”
Section: Survival Of Pig Organs and Cells Xenotransplanted In Nonhumamentioning
confidence: 99%